“Big Data” for breast cancer: where to look and what you will find - Clare, Susan E (NPJ Breast Cancer, 2016)
Accessing the massive amount of breast cancer data that are currently publicly available may seem daunting to the brand new graduate student embarking on his/her first project or even to the seasoned lab leader, who may wish to explore a new avenue of investigation. In this review, we provide an overview of data resources focusing on high-throughput data and on cancer-related data resources. Although not intended as an exhaustive list, the information included in this review will provide a jumping-off point with descriptions of and links to the various data resources of interest. The review is divided into six sections: (1) compendia of data resources; (2) biomolecular repository “Hubs”; (3) a list of cancer-related data resources, which provides information on contents of the resource and whether the resource enables upload and analysis of investigator provided data; (4) a list of seminal publications containing specific breast cancer data, e.g., publications from METBRIC, Sanger, TCGA; (5) a list of journals focused on data science that include cancer-related “Big Data”; and (6) miscellaneous resources.